THE VELARIZACIÓN IN SHIPIBO - Rocha Martinez, Rolando (2009)
Taking as an explanatory frame the presuppositions coming from the not-linear generativephonology, the phenomenon of velarización is he re described as the appearanceof a complex segment with a velar second articulation which comes into being throughthe confluence of labial sounds with an unrounded central high vowel. No other theoryhelps establish a relation of greater affinity between the phonological features and thesurface segments.